ChemInform Abstract: Photoorganocatalyzed and Visible Light Photoredox Catalyzed Trifluoromethylation of Olefins and (Hetero)aromatics in Batch and Continuous Flow. Issue 24 (27th May 2016) - Lefebvre, Quentin; Hoffmann, Norbert; Rueping, Magnus
Abstract: This reaction can be also conducted by using a photo‐flow setup which leads to significantly decreased reaction times.